Do Not Revise Ockham's Razor Without Necessity. (7th September 2016) - Baron, Sam; Tallant, Jonathan
Abstract : Ockham's razor asks that we not multiply entities beyond necessity. The razor is a powerful methodological tool, enabling us to articulate reasons for preferring one theory to another. There are those, however, who would modify the razor. Schaffer (2010: 313—our italics), for one, tells us that, 'I think the proper rendering of Ockham's razor should be 'Do not multiply fundamental entities without necessity''. Our aim, here, is to challenge such re‐workings of Ockham's razor.